2004
DOI: 10.1021/bm049577p
|View full text |Cite
|
Sign up to set email alerts
|

PLGA:Poloxamer and PLGA:Poloxamine Blend Nanoparticles:  New Carriers for Gene Delivery

Abstract: The main objective of the present work was the development of new nanoparticulate carrier systems for the delivery of plasmid DNA. These new carriers consist of a blend matrix formed by a poly(lactic-co-glycolic acid) (PLGA) copolymer and polyoxyethylene derivatives. More specifically, we have prepared nanostructures with different PLGA:poloxamer and PLGA:poloxamine compositions by an optimized emulsification-solvent diffusion technique and studied the potential of these carriers for the encapsulation and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(100 citation statements)
references
References 38 publications
8
91
0
1
Order By: Relevance
“…Majority of reported strategies employ poly(ethylene glycol) (PEG) or poly(ethylene oxide) (PEO) chains for surface modification through physical adsorption during particle formation or by covalent linkage to the core-forming polymer [e.g., copolymer of PEG/PEO with poly(lactic acid)] prior to particle formation (19,(36)(37)(38)(39)(40)(41). More recently, the possibility of introducing PEOcontaining block copolymers into the nanoparticles matrix has been achieved by intimate blending of the PEO-copolymer with the core-forming polymer prior to nanoparticulate fabrication (42,43). This method of PEO incorporation is expected to lead to partitioning of the PEO chains on the nanoparticle surface upon hydration and better stability of the PEO chains on the nanoparticle surface.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of reported strategies employ poly(ethylene glycol) (PEG) or poly(ethylene oxide) (PEO) chains for surface modification through physical adsorption during particle formation or by covalent linkage to the core-forming polymer [e.g., copolymer of PEG/PEO with poly(lactic acid)] prior to particle formation (19,(36)(37)(38)(39)(40)(41). More recently, the possibility of introducing PEOcontaining block copolymers into the nanoparticles matrix has been achieved by intimate blending of the PEO-copolymer with the core-forming polymer prior to nanoparticulate fabrication (42,43). This method of PEO incorporation is expected to lead to partitioning of the PEO chains on the nanoparticle surface upon hydration and better stability of the PEO chains on the nanoparticle surface.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, poly(lactic-coglycolic acid) (PLGA) microspheres have been used. [14][15][16] However, the problems encountered in reaching this goal were related not only to the microencapsulation technologies but also to the intrinsic nature of polyesters. Indeed, the PLGA microencapsulation technologies imply the use of organic solvents and high energy sources, thus leading to a significant degradation of the encapsulated macromolecule during the course of the PLGA hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Team work previously conducted on similar PLGA nanoparticles used in this study showed that PLGA nanoparticles with an average size of 300 nm had no detrimental effects on mammalian cells including Caco-2 cells up to a concentration range of 0.001 mg/mL [32]. Particles prepared by the emulsion solvent evaporation technique were not toxic to human glioblastoma U87MG cells at 200 &g/mL [43] or mammalian cells [44,45]. This study showed that PLGA nanoparticles are not toxic to Caco-2 cells even at relatively high concentrations, which have not been evaluated before.…”
Section: Cytotoxicity Of Plga Nanoparticles 361 Trypan Blue Exclusmentioning
confidence: 61%